Bioenergy development : issues and impacts for poverty and natural resource management - Cushion, Elizabeth (Agriculture and rural development series., 2010)
Bioenergy has been critical to humanity since the cave dwellers first used wood to cook their food and stay warm at night. Ancient forms of bioenergy ¿ firewood and cow dung patties ¿ remain primary fuel sources for rural and poor people. New sources of bioenergy including ¿black liquor¿, biodiesel, cellulosic ethanol and many more, have great promise and generate great controversy. This book gives an overview of bioenergy developments and examines the main issues and possible socioeconomic implications of these developments and their potential impacts on land use and the environment, especial.